Learning obstacles of al-Afʿāl al-Muʿrabāt among Madrasah Tsanawiyah students - Putri, Adibah Ulaya; Sopian, Asep; Supriadi, Rinaldi; Maulani , Hikmah; Alfarizi, Muhammad Faqih (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2025)
This study aims to identify the learning obstacles experienced by eighth-grade students at a Madrasah Tsanawiyah in studying the topic of al-Afʿāl al-Muʿrabāt. A qualitative approach was employed using the Didactical Design Research (DDR) method. Participants included 47 students and one Arabic teacher. Data were collected through tests and non-test instruments, including in-depth interviews. Data analysis followed Miles and Huberman’s framework, which involves data reduction, data presentation, and conclusion drawing. The findings reveal that students experienced both ontogenic and epistemological obstacles. Ontogenic obstacles included psychological factors (such as low motivation and interest) and instrumental difficulties, with technical incomprehension being the primary challenge. These findings suggest the need for instructional solutions. The study recommends the development of a DDR-based learning design tailored to students’ needs and informed by the identified learning obstacles.